Simulasi Perbaikan Tata Letak Fasilitas Produksi Untuk Meminimalisir Jarak Perpindahan di Industri Katering Nara Kitchen - Sianipar, Joshua Tito Partogi; Astanti, Yuli Dewi; Intan Berlianty (Jurnal Informasi, Sains dan Teknologi, 2024)
Nara Kitchen is a daily catering service provider with a varied menu every day. Since the Covid-19 pandemic, catering demand has increased to 130 portions per delivery. This surge in demand necessitates improvements to the layout of production facilities, as higher production volume results in increased activity between workstations. Consequently, Nara Kitchen aims to enhance the layout of its facilities to optimize production efficiency. Facility layout improvements are implemented using the Blocplan method and are simulated through a discrete systems approach. The Blocplan method designs the layout based on the proximity between departments, aiming to minimize overall travel distance. The results of the layout improvements are then simulated using Flexsim software before being implemented. The simulation outcomes demonstrate reduced weekly travel distances. The movement distance for workers traveling from the kitchen workstation to the compounding workstation has decreased by 5.33m, while workers moving from the kitchen workstation to the packing workstation experience a reduction in movement distance of 142.38m